A novel vibration measurement and active control method for a hinged flexible two-connected piezoelectric plate. (July 2018) - Qiu, Zhi-cheng; Wang, Xian-feng; Zhang, Xian-Min; Liu, Jin-guo
Highlights: A hinged two-connected piezoelectric flexible plate apparatus is constructed. A binocular vision is used to measure the vibration of the hinged flexible plate. Decoupling on measurement of the bending and torsional vibrations is realized. An RBF-NN controller is utilized in vibration suppression experiments. Abstract: A novel non-contact vibration measurement method using binocular vision sensors is proposed for piezoelectric flexible hinged plate. Decoupling methods of the bending and torsional low frequency vibration on measurement and driving control are investigated, using binocular vision sensors and piezoelectric actuators. A radial basis function neural network controller (RBFNNC) is designed to suppress both the larger and the smaller amplitude vibrations. To verify the non-contact measurement method and the designed controller, an experimental setup of the flexible hinged plate with binocular vision is constructed. Experiments on vibration measurement and control are conducted by using binocular vision sensors and the designed RBFNNC controllers, compared with the classical proportional and derivative (PD) control algorithm. The experimental measurement results demonstrate that the binocular vision sensors can detect the low-frequency bending and torsional vibration effectively. Furthermore, the designed RBF can suppress the bending vibration more quickly than the designed PD controller owing to the adjustment of the RBF control, especially for the small amplitude residual vibrations.